Chet el fuqarolari ishtirokidagi sudlarda advokat himoyasini ta’minlash masalalari - Panjiyev Asliddin Sharofiddinovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article explores the legal differences that affect the protection of foreign nationals‟ rights in judicial proceedings and their impact on court processes. Additionally, it reviews the role of international conventions, bilateral agreements, and extradition procedures in providing legal assistance to foreign nationals.